Diffusion-driven chromium isotope fractionation in ultramafic cumulate minerals: Elemental and isotopic evidence from the Stillwater Complex. (15th October 2019) - Bai, Yang; Su, Ben-Xun; Xiao, Yan; Chen, Chen; Cui, Meng-Meng; He, Xiao-Qing; Qin, Li-Ping; Charlier, Bernard
Abstract: To investigate chromium diffusion kinetics in ultramafic cumulate minerals, we analyzed the Cr elemental and isotopic compositions of olivine, orthopyroxene, and chromite from the Stillwater layered intrusion. Core-to-rim compositional profiles reveal that Cr elemental concentrations decrease from 60 to 20 ppm in olivine and from 5000–4600 to 2700–2400 ppm in orthopyroxene. These zoned Cr distributions in olivine and orthopyroxene suggest that Cr was lost by diffusion into the melt. Olivine and orthopyroxene have δ 53 Cr values ranging from –0.09 to 0.25‰ and from –0.11 to 0.07‰, respectively, higher than the values of coexisting chromite (–0.23 to –0.07‰). This isotopic disequilibrium can be explained by diffusion-driven kinetic fractionation during cooling. The preferential diffusion of light Cr isotopes from silicate minerals to the melt resulted in isotopically heavier olivine and orthopyroxene, but the kinetic diffusion between chromite and melt negligibly affected the isotopic compositions of chromite grains due to their high Cr concentrations. Modeling results based on the observed Cr contents and isotopic compositions of silicate minerals constrain the cooling time of the Peridotite Zone in the Stillwater magmatic system to have been 10–100 kyr.